A Two-year Outcome of Various Techniques of Discectomy On Complications: A Multicentric Retrospective Study - VNR Goparaju Praveen; Pritem A Rajamani; Arvind G Kulkarni; Shekhar Y Bhojraj; S. Rajasekaran; HS Chhabra; Shankar Acharya; AA Rajamani; Abhay Nene; Ajoy Prasad Shetty; P C Dey; Arun Bhanot; et al. (Journal of Minimally Invasive Spine Surgery and Technique, 2022)
Objective Various techniques of performing lumbar discectomy are prevalent, each having its rationale and claimed benefits. The authors ventured to assess the total complication rate of lumbar discectomy as well as the complication rates of individual complications, namely CSF leaks, superficial wound infections, deep wound infections, recurrence rates, re-operation rates, and wrong level surgery. Methods This was a retrospective study of patients operated using open discectomy (OD), microdiscectomy (MD), microendoscopic discectomy (MED), interlaminar endoscopic lumbar discectomy (IELD), transforaminal endoscopic lumbar discectomy (TELD), and Destandau techniques (DT) with a minimum follow-up of 2 years. The inclusion criteria were age>15 years, failed conservative treatment for 4-6 weeks, and the involvement of a single lumbar level. Results There is no statistically significant association between surgical technique and complications. The total complication rate was 12.89% in 946 operated cases. The most common complication was recurrence (5.81%), followed by re-operation (3.69%), CSF leak (1.90%), wrong level surgery (0.63%), superficial infection (0.52%) and deep infection (0.31%). There were minor differences in the incidence of complications between techniques. Conclusion This is the first study to compare the complication rates of all the prevalent discectomy techniques across the globe in 946 patients. Although there were minor differences in incidences of complications between individual techniques, there was no statistical significance. The various rates of individual complications provide a reference value for future studies related to complications following discectomy.